Biorremediación de aguas residuales con alta salinidad mediante bacterias halófilas aisladas de perfiles costeros de Ecuador - Villota Meza, Tomás David (2014)
The fishing industry in Ecuador is a very important sector for the generation of economic income. The industry’s wastewater is characterized by the presence of salts, which causes problems in the treatment. In the current research, a treatment for wastewater takes place. The water has a salt (NaCl) concentration of 2 percent. The research is carried out by the use of aerobic halophilic bacteria, which were isolated from different sampling points of the coastal profile. The isolation of bacteria involves the taking of water samples from natural sources, the creation of geo-referenced maps including data of every point, the carrying out of culture media, with the objective of finding a formula with the largest presence of bacteria, bacteria isolation and its use in wastewater treatment with high salinity. The bio-remediation experiment was executed at a laboratory scale, with synthetic wastewater, designed for simulating the conditions of salinity and organic load of the fishing industry. The main problem found in the treatment due to the salinity presence was the lack of sedimentation at the end of it. This problem was solved with a tertiary treatment, with the use of coagulants and flocculants chemicals. Among the most relevant results, there is the determination of the formula with the highest bacterial growth, and the result of the polluted- treated water analysis. Among the most important findings in the study were the determination of the best formula for bacterial growth and the result of the parameters measured in the treated water.